1998
DOI: 10.2214/ajr.171.5.9798883
|View full text |Cite
|
Sign up to set email alerts
|

Value of MR cholangiopancreatography in evaluating choledochal cysts.

Abstract: OBJECTIVE. The aim of thisretrospective studywasto clarify whetherMR cholangiopan creatography (MRCP) isa suitablereplacement for ERCP in evaluation of thecholedochal cyst. MATERIALSAND METHODS. Sixteenpatients(six adultand 10pediatric)with chole dochal cysts underwent MRCP using a half-Fourier acquisition single-shot turbo spin-echo se quence. Extent of the cyst. defects within the biliary tree, and presence or absence of the anomalous junction of the pancreaticobiliary duct were evaluated. Findings were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
67
0
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(72 citation statements)
references
References 10 publications
3
67
0
2
Order By: Relevance
“…MRCP gives information about the extent of the cyst, defects within the biliary tree, and presence or absence of the anomalous junction of the pancreaticobiliary duct. It can play an important role as a noninvasive examination and should be considered a first-choice imaging technique for evaluation of choledochal cyst [15].…”
Section: Discussionmentioning
confidence: 99%
“…MRCP gives information about the extent of the cyst, defects within the biliary tree, and presence or absence of the anomalous junction of the pancreaticobiliary duct. It can play an important role as a noninvasive examination and should be considered a first-choice imaging technique for evaluation of choledochal cyst [15].…”
Section: Discussionmentioning
confidence: 99%
“…Although endoscopic retrograde cholangiopancreatography (ERCP) has long been regarded as the gold standard for diagnosing choledochal cysts and evaluating anomalous pancreatobiliary junction, over the past ten years multiple studies have shown MRCP to be just as sensitive, if not more, than conventional cholangiography [9] . Complications include secondary biliary cirrhosis, spontaneous rupture of the cyst and cholangiocarcinoma [10,11] .…”
Section: Discussionmentioning
confidence: 99%
“…Em 1959 Alonso-Lej 5 propuseram classificação que englobava apenas cistos biliares extra-hepáticos. Essa classificação foi modificada por Todani em 1977 6 , que incorporou as dilatações intrahepáticas 1,4 .…”
Section: Discussionunclassified